Financial Performance Assessment of PT Asuransi Jiwa Syariah Jasa Mitra Abadi Tbk Using The Early Warning System (Ews) And Risk-Based Capital (Rbc) Methods For The 2021–2024 Period - Adinda Eka Devi Aurelia; Ujang Syahrul Mubarrok (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to evaluate the financial performance of PT Asuransi Jiwa Syariah Jasa Mitra Abadi Tbk during the 2021–2024 period using a financial ratio approach based on the Early Warning System (EWS) and Risk-Based Capital (RBC). This research used a descriptive, quantitative method, utilizing secondary data. The ratios analyzed in this study include the Solvency Ratio, Profitability Ratio, Liquidity Ratio, Premium Income Ratio, and Technical Ratio. The analysis results show that the company’s overall financial performance is in fairly good condition, particularly in terms of capital and solvency, although several ratios still require improvement, especially in the aspects of profitability and premium growth.